Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian pada Toko Roti The Boutique Bakery Cabang Cengkareng Jakarta Barat - Aprilliani, Siti; Ainun, Een (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The purpose of this research is to examine the impact of product quality and promotion on purchasing decisions at The Boutique Bakery, Cengkareng branch, West Jakarta, both partially and simultaneously. This study uses a quantitative method with a probability sampling technique, specifically simple random sampling, involving 100 respondents, based on Slovin's formula. Data collection methods include observation and questionnaires, while the data analysis techniques used are descriptive analysis and quantitative analysis, including multiple linear regression, correlation coefficient analysis, hypothesis testing, and coefficient of determination analysis. The findings indicate that, in partial tests, product quality has a positive and significant effect on purchasing decisions, supported by the statistical results showing that the t-value exceeds the critical t-value and the p-value is less than 0.05. Similarly, promotion also has a positive and significant effect on purchasing decisions, with similar statistical results. In the simultaneous test, both product quality and promotion together have a positive and significant effect on purchasing decisions, with the calculated F-value surpassing the critical F-value and the p-value also less than 0.05. The results of this study suggest that both product quality and promotion are important factors influencing purchasing decisions. The implication of this research is that businesses should focus on enhancing product quality and implementing effective promotional strategies to increase consumer purchasing behavior. By doing so, businesses can improve customer satisfaction, strengthen brand loyalty, and ultimately increase sales. This research provides valuable insights for marketers and business owners to develop strategies that align with consumer preferences and expectations, ultimately contributing to the growth and competitiveness of the business in the market.